Fermented Chinese formula Shuan-Tong-Ling attenuates ischemic stroke by inhibiting inflammation and apoptosis - Mei, Zhi-gang (Neural Regen Res, 2017)
The fermented Chinese formula Shuan-Tong-Ling is composed of radix puerariae (Gegen), salvia miltiorrhiza (Danshen), radix curcuma (Jianghuang), hawthorn (Shanzha), salvia chinensis (Shijianchuan), sinapis alba (Baijiezi), astragalus (Huangqi), panax japonicas (Zhujieshen), atractylodes macrocephala koidz (Baizhu), radix paeoniae alba (Baishao), bupleurum (Chaihu), chrysanthemum (Juhua), rhizoma cyperi (Xiangfu) and gastrodin (Tianma), whose aqueous extract was fermented with lactobacillus, bacillus aceticus and saccharomycetes. Shuan-Tong-Ling is a formula used to treat brain diseases including ischemic stroke, migraine, and vascular dementia. Shuan-Tong-Ling attenuated H(2)O(2)-induced oxidative stress in rat microvascular endothelial cells. However, the potential mechanism involved in these effects is poorly understood. Rats were intragastrically treated with 5.7 or 17.2 mL/kg Shuan-Tong-Ling for 7 days before middle cerebral artery occlusion was induced. The results indicated Shuan-Tong-Ling had a cerebral protective effect by reducing infarct volume and increasing neurological scores. Shuan-Tong-Ling also decreased tumor necrosis factor-α and interleukin-1β levels in the hippocampus on the ischemic side. In addition, Shuan-Tong-Ling upregulated the expression of SIRT1 and Bcl-2 and downregulated the expression of acetylated-protein 53 and Bax. Injection of 5 mg/kg silent information regulator 1 (SIRT1) inhibitor EX527 into the subarachnoid space once every 2 days, four times, reversed the above changes. These results demonstrate that Shuan-Tong-Ling might benefit cerebral ischemia/reperfusion injury by reducing inflammation and apoptosis through activation of the SIRT1 signaling pathway.